Contribution of Arm Muscle Power, Waist Flexibility to Forehand Shot Results in Table Tennis Club PTM Mandiri: Kontribusi Power Otot Lengan, Kelentukan Pinggang Terhadap Hasil Pukulan Forehand Dalam Tenis Meja Club PTM Mandiri - suheri, Indrawan; Alficandra, Alficandra (Badnur Medisa Group, 2024)
The aim of this research is to see the contribution of arm muscle power and waist flexibility to the PTM Mandiri table tennis club's forehand stroke. The type of research used in this research is correlation research. The population in this study were all PTM Mandiri club athletes, while the sampling technique in this study used total sampling, so the sample in this study was 17 people. The tests used in this research were arm muscle power tests (two hand medicine ball put), sit and reach, and table tennis forehand stroke tests. From the results of tests carried out on PTM Mandiri club athletes, the results obtained were that there was a contribution between arm muscle power to the forehand stroke of 45.60%, the remaining 54.40 was influenced by other factors, there was a contribution between waist flexibility to the forehand stroke of 38.56 The remaining 61.44% is influenced by other factors, and there is a contribution of arm muscle power and waist flexibility to table tennis forehand strokes of 72.78%, the remaining 27.22 is influenced by other factors.